WHEN RESTORATIVE JUSTICE BECOMES CASE NEGOTIATION: LEGAL VALIDITY AND NORMATIVE DISTORTION IN CRIMINAL JUSTICE - Andika Wahyudi Gani; Nurul Maghfirah Surianto (Faculty of Law, Universitas Diponegoro, 2026)
Restorative justice is normatively designed to repair harm and restore social relations among offenders, victims, and the community. However, when incorporated into formal criminal justice institutions, it may shift from a relational and reparative process into a negotiation-oriented mechanism for case resolution, particularly when institutional procedures prioritize settlement, compensation, forgiveness, or case termination over substantive restoration. This article examines that shift in the Indonesian criminal justice system, where restorative justice has been institutionalized through police, prosecutorial, and judicial regulations and further grounded in Law Number 20 of 2025 concerning the Criminal Procedure Code. Using doctrinal legal research through conceptual and statutory approaches, this article applies the Three-Pillar Institutional Legitimacy Framework, consisting of legal validity (P1), normative fidelity (P2), and public rational justification (P3). The analysis shows that Law Number 20 of 2025 strengthens the legal validity of restorative justice by regulating restorative mechanisms in Articles 79–88 and positioning prior sectoral regulations within a higher statutory framework through Articles 361 and 367. Nevertheless, legal validity alone does not guarantee substantive legitimacy. Restorative justice may still undergo normative distortion when institutional actors treat agreement, forgiveness, compensation, or procedural closure as sufficient indicators of restoration without examining victim recovery, offender accountability, voluntary participation, community involvement, guarantees of non-repetition, and the public interest. In such circumstances, public rational justification may appear coherent at the surface level while lacking normative depth. This configuration constitutes pseudo-ethical legitimacy: institutional action remains legally valid but loses the substantive restorative foundation that justifies restorative justice. This article argues that strengthening restorative justice in Indonesia requires legal harmonization and sustained institutional commitment to preserving it as a mechanism for repairing harm, restoring social relations, and preventing its reduction into a procedural tool for case disposal.